Lignin/Xylan‐Based Phase Selective Powder Gelator for Eco‐Friendly Oil Spill Treatment. (8th October 2021) - Wang, Hairong; Li, Nan; Jia, Siyu; Bian, Jing; Hao, Xiang; Peng, Feng
Abstract: Despite rapid development, oil spill agents still suffer from limitations of high cost, low adsorption ability, and non‐degradability. Herein, the alkaline lignin (AL) and hemicelluloses (xylan, Xyl) are transferred into low‐cost, green, and eco‐friendly powder gelators, featuring congealing oil ability, easy collection, and oil spill recovery. The AL and Xyl can form gels in the presence of excessive epichlorohydrin (ECH)/sodium hydroxide (NaOH) solution and subsequently self‐collapse into brittle solid when rinsed in water. After silylation treatment, the resultant powder exhibits high efficiency to congeal, a series of floating oils, as well as the great oil recovery ability. The easy availability of pulping byproducts, scalable preparation method, and excellent spill oil treatment ability hold promise for developing new bio‐based oil spill agents. Abstract : A new biomass‐derived oil gelling powder agent is developed from two byproducts of chemical pulp, alkaline lignin and industrial hemicellulose (linear xylan), featuring congealing oil ability, easy collection, and oil spill recovery. The oil gelling powder agent has a strong adsorption effect on a variety of oils and emulsions under different environments.